Designing English Handbook for the Department of Architectural Engineering and Building Information at Vocational High School - Nabila Shita Nurul Haliza; Amalia Yahya; Fadhliyah Rahmah Muin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research aimed to design an English handbook specifically for students of the Department of Architectural Engineering and Building Information. The study was conducted to address the lack of appropriate English learning materials that focus on technical vocabulary and communication skills relevant to the students’ field of study. The research employed a Research and Development (R&D) approach using the 4D model, which consists of Define, Design, Develop, and Disseminate stages. Data were collected through needs analysis, expert validation, and student responses. The final product was an English handbook containing technical vocabulary, reading texts, and practice activities related to architectural engineering and building information. The results indicated that the developed handbook was valid, practical, and suitable to support students in improving their English skills for academic and professional purposes.